MANGGIS DALAM LUKISAN REALIS KONTEMPORER - AFRI ARIN QURNIATY, Yasrul Sami, S.Sn., M.Sn. (Universitas Negeri Padang, 2019)
The creation of this final work aims to convey about the crisis the value of honesty in the realm of leadership that makes mangosteen a symbol of honesty. Through several stages of the method and process of work that are passed: (1) preparation, (2) Elaboration, (3) Synthesis, (4) Realization of the Concept, (5) Completion. The manifestation of the visualization of the final work of mangosteen in contemporary realist paintings entitled : (1) Tertinggal, (2) Dikendalikan , (3) Manggis dan Uang, (4) Manggis dan Uang#2, (5)Sengaja,(6) Kejam,(7) Batas,(8) Pecah,(9) Rapuh, (10) Keras.Keywords: mangosteen, exploration, visual.